Observation of the FeCN and FeCO Vibrations in the Active Site of [NiFe] Hydrogenase by Nuclear Resonance Vibrational Spectroscopy1. Issue 2 (8th November 2012) - Kamali, Saeed; Wang, Hongxin; Mitra, Devrani; Ogata, Hideaki; Lubitz, Wolfgang; Manor, Brian C.; Rauchfuss, Thomas B.; Byrne, Deborah; Bonnefoy, Violaine; Jenney, Francis E.; Adams, Michael W. W.; Yoda, Yoshitaka; et al.
<x xml:space="preserve">Abstract</x> Nuclear inelastic scattering of 57Fe labeled [NiFe] hydrogenase is shown to give information on different states of the enzyme. It was thus possible to detect and assign FeCO and FeCN bending and stretching vibrations of the active site outside the spectral range of the FeS cluster normal modes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>